Rhithrops capensis gen. et sp. nov., a new aquatic dryopid beetle from the Western Cape of South Africa (Coleoptera: Dryopoidea: Dryopidae) - Bilton, David T.; Shepard, William D. (Zootaxa, 2022)
Rhithrops capensis gen. et sp. nov. is described from the Matjies River, in the Cedeberg range of the Western Cape Province, South Africa. The new genus is apparently related to the South African endemic genera Rapnus Grouvelle, 1899 and Strina Redtenbacher, 1867, but exhibits a number of distinct character states, including gibbosities outside the sublateral pronotal furrows and a transversely upturned labral apex, unique within the family. Rhithrops gen. nov. was collected from around the roots of aquatic plants in fast flowing deep water runs, as well as being sampled in nocturnal drift nets. The new species has relatively long legs and well-developed tarsal claws, and appears to be adapted to an entirely aquatic, benthic existence. A revised key is provided to the dryopid genera of South Africa.